2021
DOI: 10.1186/s12967-021-03151-3
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 group IIA correlates with circulating high-density lipoprotein cholesterol and modulates cholesterol efflux possibly through regulation of PPAR-γ/LXR-α/ABCA1 in macrophages

Abstract: Background Secretory phospholipase A2 group IIA (sPLA2-IIA) is an independent risk factor for cardiovascular disease, but its role on high-density lipoprotein cholesterol (HDL-C) level has not been clarified. The aim of the present study was to explore the association between circulating sPLA2-IIA and HDL-C, and to evaluate if sPLA2-IIA enhances cholesterol efflux capacity through regulation of peroxisome proliferator-activated receptor γ (PPAR-γ), liver X receptor α (LXR-α), and ATP-binding ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“… 240 An investigation of 131 patients with coronary artery disease also revealed that the use of the PPARγ inhibitor GW9662 led to a decrease in LXR-α and ABCA1 levels in the group, accompanied by impaired cholesterol efflux capacity. 241 Cholesterol carried by HDL is eventually taken up by hepatic SR-B1 receptors after circulation and metabolized in the liver, which brings us back to the liver function discussed at the beginning of this review.…”
Section: Reverse Cholesterol Transportmentioning
confidence: 96%
“… 240 An investigation of 131 patients with coronary artery disease also revealed that the use of the PPARγ inhibitor GW9662 led to a decrease in LXR-α and ABCA1 levels in the group, accompanied by impaired cholesterol efflux capacity. 241 Cholesterol carried by HDL is eventually taken up by hepatic SR-B1 receptors after circulation and metabolized in the liver, which brings us back to the liver function discussed at the beginning of this review.…”
Section: Reverse Cholesterol Transportmentioning
confidence: 96%
“…The nuclear receptor superfamily includes ligand-activated transcription factors called peroxisome proliferator-activated receptors (PPARs) [ 28 ]; the PPAR family is subdivided into three isotypes PPARα, PPAR β/δ, and PPARƳ [ 41 ]. Activation of the PPARs subtype is essential for controlling cell proliferation, differentiation, apoptosis [ 42 ], enhancing cell development [ 43 ], and wound healing [ 44 ], raising high-density lipoprotein (HDL) levels [ 45 ], reducing triglyceride levels [ 46 ], and improving insulin sensitivity [ 47 ]. However, PPARα is widely distributed throughout the body tissues such as cardiac [ 48 ], renal, liver [ 49 ], muscles, and adipose tissue [ 50 ], which is essential for regulation of angiogenesis, inflammation, and free fatty acid catabolism [ 51 ].…”
Section: Introductionmentioning
confidence: 99%